Sociodemographic Determinants of Parents of Toddler-Aged Children on Deciduous Tooth Eruption: A Research Article - Fatkhurrohman, Fuad; Fajar Mentari, Nur A’in; Astuti , Rahayu; Khamilatusy Sholekhah, Nur (Jurnal Kesehatan Gigi, 2025)
Deciduous tooth eruption is a fundamental physiological milestone in toddler growth that indicates the maturation of the stomatognathic system. This study aimed to analyze the sociodemographic determinants of parents—specifically education, occupation, income, and health insurance ownership—on the eruption of deciduous teeth in toddlers. This analytical observational research employed a crosssectional design involving 167 toddlers in Pedurungan Tengah Subdistrict, selected via simple random sampling. Data were collected through intraoral examinations and validated questionnaires, then analyzed using the Chi-square test (p<0.05). The research findings revealed that the majority of toddlers had normal eruption patterns, yet statistical analysis showed no significant relationship between father’s education (p=0.554), mother’s education (p=0.284), father’s occupation (p=0.578), mother’s occupation (p=0.220), parental income (p=0.900), or National Health Insurance (JKN) ownership (p=0.091) with tooth eruption status. In conclusion, parental sociodemographic factors are not direct determinants of deciduous tooth eruption in this population, suggesting that biological factors or specific nutritional intake may play a more dominant role than social status. These results imply that dental health promotion should target all socioeconomic layers equally, focusing on nutritional quality rather than economic capacity.